Effect of basic nitrogen compounds on gas oil hydrodesulfurization and deposit formed on the catalyst. (1st August 2015) - Koide, Ryutaro; Iwanami, Yoshimu; Konishi, Shozaburo; Kimura, Nobuharu; Takahashi, Shinya; Kamata, Masato; Baba, Toshihide
Highlights: Residue desulfurization gas oil contained basic nitrogen compounds like anilines. Light cycle oil contained polyaromatic hydrocarbons, indoles and carbazoles. A low deactivation rate was observed for feed with residue desulfurization gas oil. The deposit from feed with light cycle oil was clarified as aromatic. Abstract: The authors studied the effect of the composition of cracked gas oils on the hydrodesulfurization to obtain clean diesel fuel. The required reaction temperature for sulfur specification of diesel fuel using a feedstock mixed with residue desulfurization gas oil (RDS-GO) was equivalent to that using light cycle oil (LCO). RDS-GO has a high content of basic nitrogen compounds, whereas LCO has a high content of aromatic hydrocarbons that are known to inhibit the hydrodesulfurization of gas oil. Using two-dimensional gas chromatography, LCO was found to contain polyaromatic hydrocarbons and non-basic nitrogen compounds, such as indoles and carbazoles, whereas RDS-GO contained monoaromatic hydrocarbons and basic nitrogen compounds, such as anilines. In a deactivation test conducted over 2300 h, the feedstock mixed with RDS-GO showed a lower deactivation rate than LCO. Raman spectroscopy, 13 C NMR, and electron energy-loss spectroscopy in transmission electron microscopy showed that the deposits formed on the used catalysts during the deactivation test with the feedstock mixed with LCO contained more aromatic compounds than those with RDS-GO. The coke in the deposits from the feed containing RDS-GO was expected to be more anisotropic than that from the LCO. The improved hydrodesulfurization activity observed with RDS-GO was attributed to its characteristic components, which are thought to inhibit the growth of coke on the catalyst.